Integrating Health Security Protocols Into Hospital Health Administration: A Study Of Nursing Leadership Roles (The Review of Diabetic Studies, 2024)
Background: The adoption of efficacious health security strategies within the management structures of healthcare institutions has become an imperative in the modern healthcare delivery system. The role of nursing leadership has been an integral component in the process of adoption of such an event in respect to preparing for and responding to emergencies within health care. This study aims to examine how the adoption of such strategies related to health security within health care has been implemented within the health care systems of these institutions through leadership in nursing.Methods: The present study employs a literature review method together with a case study approach in deriving its results. Research methodology for the study involves reviewing information regarding approaches in leadership, operative factors, issues with the application of health security, advanced practices in nursing, as well as emergency preparedness approaches in deriving a conclusion.Results: The research shows that systemic planning, involvement at a multi-level, infrastructure development, as well as funds, are necessary prerequisites to ensure an effective integration process. The key findings express certain approaches by the leadership in the sector of nursing, as well as challenges currently faced. The results make it clear that there is an important role played by the leadership in the sector of nursing, as a means to mediate policy and practices, especially within a context pertaining to issues of public health.Conclusion: The crucial role of nursing leaders in the incorporation of health security protocols into the health care management structure cannot be overemphasized. Their major strength in this regard is their capacity to traverse across the health care system in order to enhance responsiveness to threats of homeland security threats. Some concluding strategies are given in relation to improving health care security systems using the strength of nursing leaders.